2010
DOI: 10.1002/pon.1574
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural determinants of men's reactions to prostate cancer diagnosis

Abstract: Objective-To develop a better understanding of how men react to being diagnosed with prostate cancer and identify factors that influence these responses, we conducted an observational study to identify sociocultural predictors of men's psychological reactions.Methods-Participants were 70 African American and 124 white prostate cancer patients who completed a structured telephone interview that evaluated psychological reactions in terms of intrusive thoughts about cancer and attempts to avoid cancer-related tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Halbert et al found that even though men are making an active effort to suppress their thoughts about cancer, they are also trying to make sense of their diagnosis. The authors found that married men and men with a high educational level seemed to handle the message of cancer better than those living alone and with low educational level [29]. In our study, most men were married, however with limited educational background.…”
Section: Discussionmentioning
confidence: 47%
“…Halbert et al found that even though men are making an active effort to suppress their thoughts about cancer, they are also trying to make sense of their diagnosis. The authors found that married men and men with a high educational level seemed to handle the message of cancer better than those living alone and with low educational level [29]. In our study, most men were married, however with limited educational background.…”
Section: Discussionmentioning
confidence: 47%
“…In studies of men with cancer, including prostate cancer, there is clear evidence for a direct relationship between social constraints and cancer-related intrusive thoughts and avoidant disclosure behaviors (Halbert et al, 2010; Hoyt, 2009; Lepore & Helgeson, 1998). This relationship appears stable across the disease trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Furthermore, patients had different levels of desire to participate in decision-making [5] and informational needs [7] , and healthcare providers were frequently unaware of the individual patient's preferences. [10] The word "prostate" has the stigma of being directly associated with and being used as a common acronym for its diseases. [10] The word "prostate" has the stigma of being directly associated with and being used as a common acronym for its diseases.…”
Section: Discussionmentioning
confidence: 99%